TCF7L2 and CCND1 polymorphisms and its association with colorectal cancer in Mexican patients - Rosales-Reynoso, M A; Arredondo-Valdez, A R; Juárez-Vázquez, C I; Wence-Chavez, L I; Barros-Núñez, P; Gallegos-Arreola, M P; Flores-Martínez, S E; Morán-Moguel, M C; Sánchez-Corona, J (Cellular and Molecular Biology, 2016)
Accumulative evidence suggests that alterations due to mutations or genetic polymorphisms in the TCF7L2 and CCND1 genes, which are components of the Wnt signaling pathway, contributes to carcinogenesis. The present study was designated to clarify whether common single nucleotide polymorphisms (SNPs) of the transcription factor 7- like 2 (TCF7L2) and cyclin D1 (CCND1) genes are associated with colorectal cancer risk in Mexican patients. A case-control study including 197 colorectal cancer patients and 100 healthy subjects was conducted in a Mexican population. Identification of polymorphisms was made by the polymerase chain reaction-restriction fragment length polymorphism methodology. The association was calculated by the odds ratio (OR) test. The results demonstrate that patients with the T/T genotype for the rs12255372 polymorphism of the TCF7L2 gene present an increased colorectal cancer risk (OR=2.64, P=0.0236). Also, the risk analysis for Tumor-Nodule-Metastasis (TNM) stage and tumor location showed association with this polymorphism under the over-dominant model of inheritance (OR=1.75, P=0.0440). A similar relation was observed for the genotype T/T of the rs7903146 polymorphism and the rectal location of cancer (OR=7.57, P=0.0403). For the rs603965 polymorphism of the CCND1 gene, we observed a protection effect for the colon cancer location under the dominant model (OR=0.49, P=0.0477). These results reveal a significant role of the analyzed polymorphisms in the TCF7L2 and CCND1 genes on the susceptibility or protection for developing colorectal cancer in the Mexican population.